Mutual Vulnerability? Asymmetric Relationships in Biblical Anthropology - Martos, Levente Balazs (The Biblical Annals, 2022)
The 2019 PBC document views relationships between parents and children, masters and servants, “shepherds” and “the flock,” civil authority and citizens as asymmetric. The structure of the document suggests that these relationship systems are based on shared human experience and a common theological foundation: they appear to repeat the pattern of the parent-child relationship and originate in the obligation to obey God. Using the document as a starting point, I would like to outline what the concept of asymmetric relationships can mean today. In search of common perspectives, I will compare New Testament texts with the interpretation of asymmetry in today’s social ethics discourse. The inequality and asymmetry of different persons and groups seem to be an undeniable fact, causing tension that can be resolved fruitfully by parties who take responsibility for each other in the presence of a “third.”